Childhood exposure to non-persistent pesticides and pubertal development in Spanish girls and boys: Evidence from the INMA (Environment and Childhood) cohort. (1st January 2023) - Castiello, Francesca; Suárez, Beatriz; Beneito, Andrea; Lopez-Espinosa, Maria-Jose; Santa-Marina, Loreto; Lertxundi, Aitana; Tardón, Adonina; Riaño-Galán, Isolina; Casas, Maribel; Vrijheid, Martine; Olea, Nicolás; Fernández, Mariana F.; et al.
Abstract: This study assessed cross-sectional associations between urinary metabolites of non-persistent pesticides and pubertal development in boys and girls from urban and rural areas in Spain and examined effect modification by body mass index (BMI). Four metabolites of insecticides (TCPy, metabolite of chlorpyrifos; IMPy, metabolite of diazinon; DETP, non-specific metabolite of organophosphates; 3-PBA, metabolite of pyrethroids) and the metabolite of ethylene-bis-dithiocarbamate fungicides (ETU) were quantified in urine collected in 2010–2016 from 7 to 11-year-old children (606 girls, 933 boys) participating in the INMA Project. Pubertal development was ascertained by Tanner stages and/or parent-reported Pubertal Development Scale (PDS). Associations between pesticide metabolites and odds of being in stage 2+ for breast development (girls), genital development (boys), pubic hair growth (girls and boys), and/or overall puberty onset, gonadarche, and adrenarche (PDS for girls and boys) were examined by mixed-effect logistic regression. Effect modification by BMI was explored by interaction terms and stratified analysis. In girls, DETP and ETU concentrations>75th percentile (P75) were associated with higher odds of overall puberty development (OR [95%CI] = 1.86 [1.07–3.24] and 1.71 [1.03–2.83], respectively, for > P75 vs. undetected concentrations), while ETU > P75 was also associated with higher odds of breast development (OR [95%CI] = 5.55 [2.83–12.91]), particularly in girls with underweight/normal weight (OR [95%CI] = 10.08 [2.62–38.76]). In boys, detection of TCPy (40%) and 3-PBA (34%) was associated with higher odds of genital development (OR [95%CI] = 1.97 [1.08–3.57] and 2.08 [1.15–3.81], respectively), and the association with 3-PBA was observed in boys with overweight/obesity alone. In addition, ETU > P75 was associated with higher odds of genital development in boys with underweight/normal weight (OR [95%CI] = 2.89 [1.08–7.74]) but higher DETP with lower odds of puberty in boys with overweight/obesity (OR [95%CI] = 0.94 [0.89–0.99] per log-unit increase in concentration). Results suggest an association of childhood exposure to ETU and certain insecticides with earlier puberty in girls and boys that may be modified by child BMI. Graphical abstract: Image 1 Highlights: Higher urinary DETP and ETU were associated with earlier puberty development in girls. Association between ETU and breast development was stronger in normal weight girls. TCPy and 3-PBA were associated with earlier genital development in boys. Higher ETU was associated with earlier genital development in normal weight boys. Higher DETP was associated with delayed puberty development in overweight/obese boys.